ISOLATION, CLONING AND CHARACTERIZATION OF PYROPHOSPHATE-DEPENDENT PHOSPHOFRUCTOKINASE A-SUBUNIT GENES FROM SACCHARUM OFFICINARUM L. - ALAMSYAH, FIRMAN
PFP is an enzyme which catalyses the reversible conversion of fructose-6-phosphate to fructose-1,6-biphosphate, by using pirophosphate as the phosphoryl donor, in sucrose metabolism. Plant PFP generally consists of a- and B-subunit, which encoded by two different gene. a2B2 is the most active form of the enzyme and initiate the glycolytic reaction. The a-subunit play an important role in the enzyme regulation and could increases the activity of the B-subunit in the form of tetrameric a2B2. The purpose of this research was to isolate, clone and characterize the PFPa gene from sugarcane (Saccharum officinarum L.) and also to analyse the full-length PFPa gene from sugarcane, using EST database of sugarcane in GenBank. RNA and DNA were isolated from the leafroll and then amplified by RT-PCR and PCR method, respectively. RNA amplification generated 900 bp cDNA fragment and DNA amplification also generated 900 bp DNA fragment. The cDNA and the DNA were succesfully cloned. In silico analysis toward sequencing result of cDNA fragment, using BLASTx program, showed that the cDNA fragment was identified as sugarcane PFPa. The sequence of the PFPa cDNA fragment from S. officinarum, has been submitted to DNA Data Bank of Japan (DDBJ) with accession number AB270695. In silico analysis using BLASTn program toward sugarcane EST database in GenBank, resulting full-length PFPa cDNA sequence of sugarcane, 2242 bp in length. Full-length PFPa protein sequence of sugarcane showed the conserved binding site for pyrophosphate and fructose-6-phosphate. In silico analysis using ClustalX program ver. 1.83, showed that the PFPa DNA fragment of sugarcane has no intron. Two gene trees of PFPa cDNA and protein, which constructed by parsimony method in PHYLIP program ver. 3.573c, form two separated cluster of Magnoliopsida and Liliopsida, supported by high bootstrap values.